Effect of fishing effort on the trophic functioning of tropical estuaries in Brazil. (31st October 2022) - Lira, Alex Souza; Lucena-Frédou, Flávia; Lacerda, Carlos Henrique Figueiredo; Eduardo, Leandro Nolé; Ferreira, Valdimere; Frédou, Thierry; Ménard, Frédéric; Angelini, Ronaldo; Le Loc'h, François
Abstract: A trophic web is a network of complex interactions and energy links between species. These interactions can be simplified into trophodynamic models, such as Ecopath (EP) and EcoTroph (ET), important tools providing the holistic view needed for the ecosystem approach to fisheries. We described food web structure and trophic interactions by developing an EP model for the Santa Cruz Channel (SCC), a large tropical estuarine system in northeastern Brazil, surrounded by mangroves and highly subject to the impacts of domestic pollution, industry, artisanal fisheries, and aquaculture. In addition, considering ecological and fisheries perspectives, we developed ET models in three neighboring Brazilian estuaries (SCC; Sirinhaém – SIR and Mamanguape – MAM) to explore levels of exploitation that affect their trophic functioning. Our EP and ET models consisted of 32 compartments (three primary producers, six invertebrates, 22 fish, and detritus). Keystone Index and Mixed Trophic Impact analysis pointed that several groups of commercial relevance are also ecologically relevant and lack fishing regulations, such as Snooks ( Centropomus spp.), Jacks ( Caranx spp.) and Barracudas (Sphyraena spp). Fishery impacts across the trophic level spectrum differ between ecosystems, which causes top-down effects depending on the exploitation dynamics of each system. The fishing pressure affects mainly the low and intermediate Trophic Level (TLs) in MAM and SCC and high TLs in the SIR estuary. Consequently, a decrease of biomass for low and high TL was found with the increasing of fishing effort, respectively. These findings are an important contribution to the trophic modelling of tropical estuaries, indicating that both EP and ET approaches can be effective tools to improve the understanding of the trophic functioning and fishery effect on estuarine ecosystems. Additionally, increasing the knowledge of key ecosystem processes in estuarine systems may help to enhance conservation initiatives for sustainable use of the ecosystem, such as protected areas, temporal control of fishing, and the catch size limit. Highlights: Santa Cruz Channel estuary, Northeast Brazil, is an immature and resilient ecosystem. The snooks, jacks and Barracudas, were key species in Santa Cruz Channel estuary. Filter-feeders and invertebrates had the highest catches reducing the TL of the catch. Fishery impacts in the trophic level spectrum differ between ecosystems. The fishing pressure affects mainly the low and intermediate TLs.